A computer aided drawing system evaluation with early and late blind users. Issue 4 (4th July 2022) - Fernando, Sandra; Ohene-Djan, James
ABSTRACT: The present lack of suitable and efficient graphics creation techniques may place limitations on the career progression and life contentment of blind students. It is challenging for a BVI (Blind and Visually Impaired) person to draw diagrams or art, which are commonly taught in education or used in industry. The SETUP09 graphics creation system was developed to address a need for blind users to be able to create such content and consists of both navigation and computer aided drawing techniques, enabling graphics creation and manipulation through command language and intuitive, matrix-style movement. The technique can facilitate a user's ability to produce art and scientific diagrams electronically. This paper presents a comparative system evaluation of digital versus analogue drawing techniques with early and late blind individuals. Users were tested using different graphics creation tasks to assess the accuracy and efficiency of an analogue drawing technique compared with the digital SETUP09 system. The results confirmed that the SETUP09 compass-based graphics creation technique allows greater accuracy in completing a drawing task, with a noticeable reduction in effort compared to analogue drawing techniques.